Cardiovascular Risk and Sudden Sensorineural Hearing Loss: A Systematic Review and Meta‐Analysis. (25th April 2022) - Simões, João Filipe Carvalho Pereira Mano; Vlaminck, Stephan; Seiça, Raquel Maria Fino; Acke, Frederic; Miguéis, António Carlos Eva
Abstract : Objectives/Hypothesis: It was previously suggested that patients with idiopathic sudden sensorineural hearing loss (ISSNHL) have a higher risk of cardiovascular disease. The aim of this study is to determine if ISSNHL patients have an increased cardiovascular risk by means of a systematic review and meta‐analysis. Methods: A systematic literature review was performed using PubMed, Embase, Cochrane Libraries and Web of Science. Studies with a clear definition of ISSNHL, investigating an association between traditional vascular risk factors and ISSNHL were included. Adhering to Preferred Reporting Items for Systematic Reviews and Meta‐analysis (PRISMA) guidelines, two reviewers extracted the data, assessed the risk of bias and performed the analysis of the collected evidence. Results: Nineteen case–control studies and two cohort studies were included (102, 292 patients). Individual studies argued for higher prevalence of hypercholesterolemia, diabetes mellitus (DM) and higher blood pressure (HBP) in ISSNHL patients with a range of odds ratios (ORs) from 1.03 to 19. Pooled analysis of adjusted ORs revealed a significantly increased risk of ISSNHL for patients with hypertriglyceridemia (OR 1.54; 95% confidence interval [CI] 1.18–2.02) and high levels of total cholesterol (TC) (OR 2.09; 95% CI 1.52–2.87 after sensitivity analysis), but not for HBP, DM, or high levels of low‐ and high‐density lipoproteins. Conclusion: An association between higher vascular risk profile and ISSNHL seems apparent in high levels of triglycerides (TG) and TC, but more studies are needed to confirm this hypothesis due to the high levels of data heterogeneity in the literature. Level of Evidence: NA Laryngoscope, 133:15–24, 2023